MY SAY: Challenging the status quo - Abd Razak, Dzulkifli (2009)
On Oct 23, Malaysians were presented with Budget 2010 aptly themed " 1Malaysia, Together We Prosper". The budget is based on a threepronged strategy: driving the nation towards a highincome economy; ensuring holistic and sustainable development, and focusing on the people's wellbeing. Prime Minister and Finance Minister Datuk Seri Najib Razak said in his budget speech: "This means the needs of the people must always take precedence. Therefore, every step requires sacrifice and strong cooperation from every segment of society." He emphasised that the government would take a new approach based on innovation, creativity and highvalued activities.